Rapid Emulation of Spatially Resolved Temperature Response to Effective Radiative Forcing - Christopher B. Womack; Paolo Giani; Sebastian D. Eastham; Noelle E. Selin (Journal of Advances in Modeling Earth Systems)
Abstract Effective assessment of potential climate impacts requires the ability to rapidly predict the time‐varying response of climate variables. This prediction must be able to consider different combinations of forcing agents at high resolution. Full‐scale ESMs are too computationally intensive to run large scenario ensembles due to their long lead times and high costs. Faster approaches such as intermediate complexity modeling and pattern scaling are limited by low resolution and invariant response patterns, respectively. We propose a generalizable framework for emulating climate variables to overcome these issues, representing the climate system through spatially resolved impulse response functions. We derive impulse response functions by directly deconvolving effective radiative forcing and near‐surface air temperature time series. This enables rapid emulation of new scenarios through convolution and derivation of other impulse response functions from any forcing to its response. We present results from an application to near‐surface air temperature based on CMIP6 data. We evaluate emulator performance across 5 CMIP6 experiments including the SSPs, demonstrating accurate emulation of global mean and spatially resolved temperature change with respect to CMIP6 ensemble outputs. Global mean relative error in emulated temperature averages 1.49% in mid‐century and 1.25% by end‐of‐century. These errors are likely driven by state‐dependent climate feedbacks, such as the non‐linear effects of Arctic sea ice melt. We additionally show an illustrative example of our emulator for policy evaluation and impact analysis, emulating spatially resolved temperature change for a 1,000 member scenario ensemble in less than a second.